Penilaian Keberhasilan Usaha Industri Mikro Kecil Menengah Makanan Ringan Kota Sukabumi dengan Importance Performance Analysis (IPA) - Ujang Heri Rahmatullah; Dwi Gemina; Tini Kartini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the assessment of the success of small and medium-sized snack food industry businesses in Sukabumi City. The samples were taken from 50 Snack Food UMKM/IMKM registered with the Sukabumi City Cooperatives, Industry and Trade Service. The method used in this research is descriptive qualitative methods. The research results show that based on Importance Performance Analysis (IPA), two attributes have been identified that must be prioritized, such as having the ability to grow the business (management, financial, administrative, sales skills, creating competitive products), and being oriented towards the future (Vision and Mission, business goals). In addition, the sub variable of business success based on Importance Performance Analysis (IPA), that must be prioritized is the Education sub variable.